Experiências na família de origem, esquemas iniciais desadaptativos e violência conjugal - Paim, Kelly Cardoso (Universidade do Vale do Rio dos Sinos, 2014)
The violent relationship between couples has been understood as a public health problem worldwide and, over the past few years, many studies are devoted to understanding the phenomenon. However, there is no unanimity about the variables that explain the marital violence, also revealing a lack of explanatory studies that help in the development of more effective interventions. Starting from the assumption that marital violence dynamics is a complex and interactional phenomenon, this dissertation aims to identify variables that explain the development and maintenance of violent dynamic between couples, especially the Early Maladaptive Schemas proposed by Jeffrey Young in Schema Therapy. The document is composed of two articles. In the first one, is exposed discriminant profile among subjects with a history of physical violence against intimate partners and subjects without historic. On the second, we investigate the power of experiences in the family of origin and Initial Maladaptive Schemas as predictors of physical violence in the marital relationship between men and women. The results showed that Early Maladaptive Schemas, especially the first schematic domain, are fundamental variables for understanding the intimate physical violence. Thus, we believe that the results help in understanding the dynamics of violent relationships, contributing to the development of intervention and prevention programs. It is suggested that therapeutic treatments for couples in a violent situation should be based on interventions that go beyond the violent behaviors, but also consider the Early Maladaptive Schemas.
Family-of-origin experiences, early maladaptive schemas and marital violence
Keywords: Violência conjugal; Esquemas iniciais desadaptativos; Casais; Relacionamento conjugal; Marital violence; Family-of-origin experiences; Early maladaptive schemas; Couples; Married couples; ACCNPQ::Ciências Humanas::Psicologia